answersLogoWhite

0


Best Answer

4y + 3w + 4x + 9y + 7x - 7w (combine like terms)
-4w + 11x + 13y

User Avatar

Wiki User

โˆ™ 2009-12-10 14:50:42
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is 4y plus 3w plus 4x plus 9y plus 7x-7w?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is the answer to 8x-5w plus 4x plus 9y plus 4y plus 2w?

It can be simplified to: 12x-3w+13y


What is the equation for -4x plus 4y equals plus 1?

-4x + 4y = 1


How much is (2x plus 3y) plus (4x plus y)?

It is the same as: 6x+4y


What is 4(x plus y)?

4x + 4y


You write 4x plus 4y equals 40?

How do you write 4x plus 4y equals 40 or how do you solve it? You would write it 4x+4y=40 you would solve it for y by subtracting 4x from both sides 4y=40-4x then divide all of that by 4y=40-4x/4 that's if you were graphing i have no idea what you're asking hope that helps if it's not too late.


How do you solve 4x - 4y plus 7 equals 15?

4x - 4y + 7 = 15to get it into y-intercept form do this...4x -4x - 4y + 7 - 7 = 15 - 7 - 4x-4y = 8 - 4x-4y / -4 = (8 / -4) + (-4x / -4)y = x + 2you did not give any values to plug in so this is as best an answer i can give


Simplified form of -6 plus 3x minus y minus 4x plus 4y plus 5?

-6 + 3x - y - 4x + 4y + 5 (combine like terms) = (-6 + 5) + (3x - 4x) + (-y + 4y) = -1 - x + 3yHope this helps :)


What is this equation in standard form 4y equals -6 plus 4x?

In standard form it is 4x - 4y = 6 or 2x - 2y = 3


How do you solve 2y equals 4x plus 4?

2y = 4x + 4y = 2x + 2


What does -x plus 4y-3x equals?

1


Adding polynomials 3x plus 4y plus x plus 3y?

4x+7y


Simplify 4x plus 7y plus 2x-3y equals?

6x plus 4y


What is the substitution of4x plus 4y equals 16 and y equals 5?

4x+4y=16 y=5 4x+ 20=16 4x=-4 x=-1


What is the greatest common factor of 4x plus 4y?

The GCF is 4.


What is 2x(2x plus 4y)?

It is equivalent to 4x^2 +8xy


What is the ordered pairs for the equations 5x plus 4y equals 73 and -4x plus 4y equals -8?

(9,7) by Kayla hamilton


What is this expression but simplified 3x minus 4y minus x plus 6y plus 2 plus 4x?

Collect like terms: 3x - x + 4x - 4y + 6y + 2 = 6x + 2y + 2


Factor 4x-4y-ty plus xt?

4x-4y-ty+xt = 4x+tx-4y-ty = x(4+t) - y(4+t) = (x-y)*(4+t)


4(x plus y) using distributive property?

It is 4x + 4y.


Simplify the algebraic expression 4x plus 3y - 2x - 7y?

4x + 3y - 2x - 7y2x - 4y


How do you rewrite -3X plus 4Y equals 11?

4y = 3x+11 or as y = 3/4x+11/4


Factor 4x squared plus 8xy plus 4y squared?

4(x+y)^2


What is 10x plus 3y minus 4x minus 7y equals?

6x - 4y


X square plus 4x plus xy plus 4y?

In order to combine terms, the variable(s) must be the same and the exponent(s) must be the same on the variables. Since you have an x2 term, x term, xy term and y term, none of the terms can be combined. So, the answer is: x2 + 4x + xy + 4y. The only thing you could do in this problem is to factor out a 4 from the 4x & 4y so another way to write this is: x2 + xy + 4(x + y).


What is the measure of the third side of a triangle where the perimeter is 8X plus 4Y and the others are X plus 2Y and 3X plus Y?

The perimeter of the triangle is 8x + 4y. The measures of two of the sides are x + 2y and 3x + y. If these two sides were added together, they would be 4x + 3y:x + 2y3x + y4x + 3yThe third side is the perimeter minus the two known sides, so 8x + 4y - (4x + 3y). Distribute the negative: 8x + 4y - 4x - 3y. This is equal to the third side, which is 4x +y.